Investment on Farm Mechanization Intensifies Cropping and Enhance Farmer’s Income: A Meso Analysis from Semi-arid Tropics of India: RESEARCH PAPER - Shekhawat, Ravindra Singh; Rathore, Vijay Singh; Kumar, Dinesh; Singh, K.N.; Lama, Acahl; Gurung, Bishal; Choudhary, Bishwa Bhaskar (Annals of Arid Zone, 2025)
Despite the gloomy prospects for farm tractor use in the irrigated region of India depicted in studies from the 1970s and 1980s, over time the region’s farmers have adapted tractor technology innovatively and used it for many purposes. Over one third of India’s geographical area i.e. 116.4 m ha is in the semi-arid tropics in India which support about 265 m people in the rural areas. Low and unpredictable rainfall, combined with extreme temperatures and intense solar radiation, render these regions among the most vulnerable in India. In Semi-Arid Tropic India, tractors are widely used for farming operation, rural transportation and for various non-farm activities in urban areas, as well. This study analyzes the determinants of the tractor use as well as consequence of tractors on crop productivity, and the intensification of agriculture in SAT India. Panel regression model used to study the impact and determinants of tractor use in SAT India. Data was collected from Village Dynamics of South Asia (VDSA) published by ICRISAT. Tractor use across the semi-arid region of India was positively affected by the amount of institutional credit, higher cropping intensity, and higher literacy of HH head. It was concluded that tractor use has positively impacted both the intensification of agriculture and farm productivity. Further, it is revealed that, uses of the tractor in SAT India is helping in increasing farm productivity and cropping intensity. Tractor intensity grew at a fast pace even in low-wage regions of India, indicating that relatively lower labor wages might not have been a binding factor for diffusion of farm machinery and tractors among smallholding farmers in India.